2015
DOI: 10.1021/jp511637a
|View full text |Cite
|
Sign up to set email alerts
|

Single Ag Nanoparticle Spectroelectrochemistry via Dark-Field Scattering and Fluorescence Microscopies

Abstract: The spectroelectrochemical properties of individual luminescent, plasmonic silver nanoparticles (Ag NPs) are investigated using the combined methods of dark-field scattering (DFS) and photoluminescence (PL) spectroelectrochemistry. Individual NP light scattering and PL intensities are measured while the substrate’s electrochemical potential is controlled to produce and oxidize the NPs. The spectroelectrochemical responses of individual NPs are used to study heterogeneities in their redox properties not visible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
72
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(75 citation statements)
references
References 39 publications
3
72
0
Order By: Relevance
“…[10] Electrochemical studies at the single particle level are of great interest because they reveal particle-to-particle heterogeneity and provide an understanding of the underlying mechanisms that may be hidden in ensemble electrochemical measurements. [14][15][16][17][18][19][20][21][22][23][24] Recently, Zhang et al [25] . [14][15][16][17][18][19][20][21][22][23][24] Recently, Zhang et al [25] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10] Electrochemical studies at the single particle level are of great interest because they reveal particle-to-particle heterogeneity and provide an understanding of the underlying mechanisms that may be hidden in ensemble electrochemical measurements. [14][15][16][17][18][19][20][21][22][23][24] Recently, Zhang et al [25] . [14][15][16][17][18][19][20][21][22][23][24] Recently, Zhang et al [25] .…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] Several other groups have also studied the oxidation of single Ag NPs using electrochemical, optical, and correlated electrochemical-optical methods . [14][15][16][17][18][19][20][21][22][23][24] Recently, Zhang et al [25] . and Kwon et al [26] showed that oxidizing Ag NPs at highly positive potentials (> 1 V vs. Ag/AgCl) at a Au/Pt ultramicroelectrode (UME) produces Ag x O y on the surface of the Ag NPs, which then catalyzes water oxidation or hydrazine oxidation reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Independent studies on optical and electrochemical properties of single AgNPs have been conducted . However, few studies have combined electrochemistry with the spectroscopic observation of a single metal nanoparticle …”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12] However,f ew studies have combined electrochemistry with the spectroscopic observation of as ingle metal nanoparticle. [13][14][15] Dark-field microscopy (DFM), which provides the possibility of real-time opticals ensing with high sensitivity,h as been used to track andd irectly observe chemical reactions on single plasmonic nanoparticles. [17][18][19][20][21][22][23] Mulvaney and co-workersh ave demonstrated that it is feasible to modulate the optical properties of single gold nanorods by using electrochemical charge injectiont od irectly observe ar edox reactiono ns ingle gold nanorod in real time using DFM.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it provides an opportunity to monitor the changes occurring on the NPs, for example, the in situ growth, etching, and chemical reactions. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] Therefore, from the perspective of photocatalysts' synthesis, the growth of the semiconductor or metal could be monitored in real-time via dark-eld microscopy (DFM) by tracking the LSPR scattering variation. It will provide comprehensive understanding of the growth mechanism, as well as tailor the properties of photocatalysts precisely.…”
Section: Introductionmentioning
confidence: 99%